2017
DOI: 10.1371/journal.pone.0188290
|View full text |Cite
|
Sign up to set email alerts
|

3D multi-view convolutional neural networks for lung nodule classification

Abstract: The 3D convolutional neural network (CNN) is able to make full use of the spatial 3D context information of lung nodules, and the multi-view strategy has been shown to be useful for improving the performance of 2D CNN in classifying lung nodules. In this paper, we explore the classification of lung nodules using the 3D multi-view convolutional neural networks (MV-CNN) with both chain architecture and directed acyclic graph architecture, including 3D Inception and 3D Inception-ResNet. All networks employ the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
91
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(106 citation statements)
references
References 29 publications
(24 reference statements)
0
91
1
6
Order By: Relevance
“…AI has recently been applied in the medical field, such as in the diagnosis of pulmonary nodules on computed tomography, 20 diagnosis of skin cancer, 21 classification of retinal lesions based on fundus photographs, 22 endoscopic imaging diagnosis, detection of gastric cancer, 13 evaluation of Helicobacter pylori infection of the stomach, 14 classification of colon polyps, 15 and automatic classification of regions in the upper gastrointestinal endoscopic images. 23 Diagnosis of prostate cancer lesions on prostate magnetic resonance imaging has been attempted in the field of urology, 24 but only one study from the urologic endoscopy field has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…AI has recently been applied in the medical field, such as in the diagnosis of pulmonary nodules on computed tomography, 20 diagnosis of skin cancer, 21 classification of retinal lesions based on fundus photographs, 22 endoscopic imaging diagnosis, detection of gastric cancer, 13 evaluation of Helicobacter pylori infection of the stomach, 14 classification of colon polyps, 15 and automatic classification of regions in the upper gastrointestinal endoscopic images. 23 Diagnosis of prostate cancer lesions on prostate magnetic resonance imaging has been attempted in the field of urology, 24 but only one study from the urologic endoscopy field has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…al [173] used specialized CNN architectures like ResNet for detecting malarial parasites in thin blood smear images. Kang et al [174] improved the performance of 2D CNN by using a 3D multi-view CNN for lung nodule classification using spatial contextual information with the help of 3D Inception-ResNet architecture.…”
Section: Medical Image Processingmentioning
confidence: 99%
“…DeepLung [36] uses combination of dual path network [37] and gradient boosting machine to classify lung nodules. [38] adopts Multi-View-One-Network strategy in 3D CNN architecture for lung nodule classification, and realize 3D inception and 3D Inception-ResNet for this classification task.…”
Section: Lung Nodule Ct Image Classification Algorithmsmentioning
confidence: 99%